Mechanisms of Social Normalization of Violence Against Women in Libyan Society: An Analytical Sociological Approach (Comprehensive Journal of Science, 2026)
This study aims to analyze the mechanisms of social normalization of violence against women in Libyan society through an analytical sociological approach that focuses on understanding how violent practices transform into familiar and socially acceptable behaviors. The study employs the descriptive analytical method in its critical form, utilizing content analysis tools and systematic review of Arabic and international sociological literature.The study examines the multiple forms of violence against women (physical, psychological, economic, social, sexual, and symbolic) and analyzes the social and cultural factors responsible for its persistence, focusing on the role of social norms, inherited traditions, cultural values, daily practices, and patterns of socialization in producing and normalizing violence.The study reveals the existence of a "circle of normalization and reproduction" of violence, beginning with norms and values that legitimize male dominance, transmitted through socialization, embodied in daily practices, reinforced by mechanisms of social silence and institutional weakness, ultimately producing more entrenched norms. The study concludes that confronting this phenomenon requires multi-level intervention (cultural, social, institutional, epistemic) that goes beyond narrow legal approaches to fundamentally address the cultural and social dimensions that allow violence to persist and become normalized.The study presents a set of practical recommendations to enhance social awareness, develop educational curricula, rehabilitate institutions, and support scientific research, aiming to break the circle of normalization of violence and contribute to building a more just and equal society.
Keywords: Social Normalization; Violence Against Women; Libyan Society; Social Norms; Symbolic Violence; Gender; Socialization